2018
DOI: 10.1038/s41598-018-29795-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ewing Sarcoma treatment outcome using attenuated tissue reflection FTIR tissue spectroscopy

Abstract: Ewing sarcoma is the second most common type of primary bone cancer and predominantly affects children and young people. Improved outcome prediction is key to delivering risk-adjusted, appropriate and effective care to cancer patients. Advances in the Fourier Transform Infrared (FTIR) spectroscopy of tissues enable it to be a non-invasive method to obtain information about the biochemical content of any biological sample. In this retrospective study, attenuated tissue reflection FTIR spectroscopy of biopsy sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Our earlier work [21,22] focused on applying statistical approaches to study the prognostic ability of FTIR. These statistical models are based on assumptions drawn from the underlying problem and have concentrated on specific changes to peak intensities or wavelength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier work [21,22] focused on applying statistical approaches to study the prognostic ability of FTIR. These statistical models are based on assumptions drawn from the underlying problem and have concentrated on specific changes to peak intensities or wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the peak absorbance maxima in the bio-fingerprinting region (1000–1100 cm −1 ) of FTIR spectra of Ewing sarcoma bone sections can be predictive of patient outcome. [21,22] Following on from this, we considered whether treatment outcome might be better predicted by the analysis of the whole FTIR spectra. Herein we report a small-cohort retrospective study into the prognostic value of the whole spectrum obtained from ES tumours before and after neoadjuvant chemotherapy administration in combination with data-reduction and machine learning approaches.…”
Section: Introductionmentioning
confidence: 99%
“…ES is a cancer of the bones and muscles, but it also occurs in soft tissues (30,31). ES is the second most common primary malignant bone tumor in children and adolescents, with 2.9 people per million diagnosed with ES annually worldwide (32). The metastasis rate is ES was 20–25%, and the recurrence rate is 30–40% (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…It is a devastating, poorly differentiated, and high-grade osteolytic disease threatening human health severely 1,2. Statistically, ES is a rare, aggressive bone neoplasm, and around 2.9 people per million encountered with ES annually worldwide, and predominantly appeared in childhood and adolescence 3,4. ES mainly occurs in bone and surrounding soft tissue characterized by a highly aggressive small round blue cell malignant neoplasm 5,6.…”
Section: Introductionmentioning
confidence: 99%